IMPLEMENTATION OF STRATEGIC MANAGEMENT ACCOUNTING IN STRENGTHENING INNOVATION AND INFRASTRUCTURE OF MSMES IN DISADVANTAGED, FRONTIER, AND OUTERMOST REGIONS TO ACHIEVE DECENT WORK AND ECONOMIC GROWTH - Yanuar Ramadhan; Shalma Ridanti; Juwita Dwi Maulidia Arisliani (Universitas Nusa Cendana, 2025)
This study examines the role of Strategic Management Accounting (SMA) in enhancing innovation and infrastructure development for Micro, Small, and Medium Enterprises (MSMEs) located in Disadvantaged, Frontier, and Outermost Regions. The objective is to support the achievement of Sustainable Development Goals (SDGs), specifically SDG 8 on decent work and economic growth and SDG 9 on industry, innovation, and infrastructure. Using a systematic literature review of 13 journal articles published between 2020 and 2025, the findings show that SMA contributes significantly to strengthening financial literacy, resource utilization, and managerial capabilities of MSMEs. SMA also promotes digital transformation and collaboration among stakeholders, enabling broader market access and the formation of an inclusive business ecosystem. From the Resource-Based View (RBV), SMA acts as a strategic approach to managing unique and hard-to-imitate internal resources, thus fostering sustainable competitive advantage. Overall, SMA supports innovative, competitive, and resilient local economic development. Keywords: Strategic Management Accounting; MSMEs; SDG 8; SDG 9; Disadvantaged; Frontier; Outermost Regions; Sustainable Development Goals